2020
DOI: 10.1155/2020/2345970
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Antibreast Cancer Mechanism and Bioactive Components of Si-Wu-Tang by Cell Type‐Specific Molecular Network

Abstract: Si-Wu-Tang (SWT), a traditional Chinese herbal formula, has shown an effect on antibreast cancer. However, the mechanisms and bioactive components of SWT are still unclear. Fortunately, cell type-specific molecular network has provided an effective method. This study integrated the data of formula components, all types of biomolecules in the human body, and nonexpressed protein in breast cancer cells and constructed the breast cancer cell network and the biological network that SWT acted on the breast cancer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…VERB interacted with Sterile Alpha Motif Domain 3 (SAMD3), which is protein-coding gene, resulting in its phosphorylation, which in turn could hinder the cell proliferation. Additionally, VERB shown to promote the expression of activator protein 1 (AP-1), which can regulates a number of cell processes, including proliferation, differentiation and apoptosis; activated AP-1 can reduce the gene expression MYC (an oncogene) and CDk6, which is an important key in the progression of the cell cycle [54].…”
Section: Breast Cancermentioning
confidence: 99%
“…VERB interacted with Sterile Alpha Motif Domain 3 (SAMD3), which is protein-coding gene, resulting in its phosphorylation, which in turn could hinder the cell proliferation. Additionally, VERB shown to promote the expression of activator protein 1 (AP-1), which can regulates a number of cell processes, including proliferation, differentiation and apoptosis; activated AP-1 can reduce the gene expression MYC (an oncogene) and CDk6, which is an important key in the progression of the cell cycle [54].…”
Section: Breast Cancermentioning
confidence: 99%
“…Of note, SWT has an anti-cancer effect (Shan et al, 2021) [ 11 ]. A number of previous studies have indicated that the molecular mechanism of SWT against breast cancer is closely related to its potential effects on modulation of estrogen activity [ 12 , 13 ]. By regulating ER pathway, the expression level of estrogen receptor β subtype (ER β) protein is increased, and the ratio of ER α/ER β is reduced, thus leading to the attenuation of the growth of estrogen-dependent tumor cells [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…VB has recently received considerable attention owing to its significant clinical value, including antioxidative, antiinflammatory, antibacterial, and antifungal properties (8)(9)(10)(11)(12). Moreover, VB also possesses anti-tumour activity against various cancers, such as glioblastoma, prostate cancer, and breast cancer (13)(14)(15)(16)(17). For example, VB has an anti-tumour role in breast cancer by suppressing cell proliferation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, VB also possesses anti-tumour activity against various cancers, such as glioblastoma, prostate cancer, and breast cancer (13)(14)(15)(16)(17). For example, VB has an anti-tumour role in breast cancer by suppressing cell proliferation (16). VB can effectively inhibit cell growth and migration, and promote cell apoptosis and autophagy in glioblastoma (15).…”
Section: Introductionmentioning
confidence: 99%